Pendekatan Algoritma Genetika pada Optimalisasi Pekerjaan Bangunan Air - Sapta, Ricky Indra; Winanda, Lila Ayu Ratna; Roostrianawaty, Nenny; Santosa, Febrian Aditama (Jurnal Talenta Sipil, 2025)
The Cijurey Dam in Bogor Regency, West Java, is a national strategic project aimed at overcoming flooding problems and increasing water availability for agriculture and daily needs. The construction of this dam requires optimization of the use of heavy equipment, especially in spillway excavation work, in order to increase efficiency and reduce operational costs, therefore this study aims to develop a model for optimizing the use of heavy equipment in water construction projects. This study uses the Genetic Algorithm (GA) method implemented in the MATLAB application to design an optimization model for the placement of heavy equipment, including hydraulic excavators, bulldozers, and dump trucks. Primary and secondary data were collected for the analysis of the performance of the heavy equipment used, with a focus on the combination of equipment and its capacity. The results of the study show that the application of GA is able to produce the most efficient combination of heavy equipment, with measurable operational time. This study emphasizes the importance of using algorithms in dam construction projects, as an innovative step to increase productivity and efficiency in the construction industry.